New synonyms in the genus Lopholejeunea (Lejeuneaceae, Marchantiophyta) - Sass-Gyarmati, Andrea (Phytotaxa, 2020)
Lopholejeunea (Stephani 1890: 285) is a pantropical genus with 42 species and one variety (Söderström et al., 2016), of which 12 species have been recorded from Madagascar (Marline et al., 2012). During examination of various Lopholejeunea materials from Madagascar, a few nomenclatural changes became necessary. As a result, ten species are accepted for Madagascar: Lopholejeunea borbonica Stephani (1896: 109), L. erugata Thiers (1984: 174), L. eulopha (Taylor 1846: 391.) Schiffner (1893: 129), L. grandicrista Stephani (1893: 34), L. leioptera Sass-Gyarmati (2001: 80), L. lepidoscypha Kiaer et Pearson (Pearson 1892: 5), L. nigricans (Lindenberg in Gottsche et al. 1845: 316) Schiffner (1898: 293), L. onraedtii Vanden Berghen (1984: 452), L. subfusca (Nees 1830: 36) Schiffner (1897: 593) and L. utriculata Stephani (1912: 69).